PENINJAUAN ANGGARAN UNTUK MENYESUAIKAN KEMAMPUAN KINERJA KEUANGAN DAN MENGENDALIKAN MANAJEMEN PERUSAHAAN PADA PT. TOR GANDA - AHMAD SAYUTI PULUNGAN; HERY DIA ANATA BATUBARA; FEBRIANDO SIREGAR (JURNAL ILMIAH KOHESI, 2021)
The purpose of this research is to review the budget in adjusting financial performance capabilities and controlling ptmanagement. DOUBLE TOR. The results prove that the budgeting in the company, especially the production cost budget in2015 is too high compared to its realization and in accordance with the capabilities made by the company so that thecompany can implement effective management control to support the drafting of the budget and the company is able to carryout the process of strategic planning, organizing, briefing and controlling the use of resources to realize the company'sbudget. The results of budget evaluation can support adjustment of financial performance capability and management controlat PT. TOR GANDA, because the company's budget can be more realistic and in accordance with the company's financialperformance capabilities so that the preparation of the company's budget can ultimately improve the company's financialperformance.